Rethinking Border Studies: Participation and Social Innovation in Border Zone Development - Luís do Espírito Santo, Anderson; Voks, Douglas (Organizações & Sociedade, 2021)
The study of emerging forms of public engagement and collective action is crucial for understanding the ongoing democratic dynamics, citizenship, and the constitution of the city's public problems. To recognize how the field of frontier studies is inseparable from the processes of experience of actors, this study focuses on the importance of the social innovation ecosystem (SIE) for the development of frontier zones. Specifically, this study revisits the main instruments of public management and border development policies to emphasize figures of civil society and their collective mobilizations on the Brazil-Bolivia border, recognizing social innovation initiatives and the main challenges they seek to solve. This path of public investigation allowed us to understand the territorial dimension of borders and expand their meaning as a living space by giving light to the actors' practices, identifying how they mobilize to repair socio-environmental inequalities.